PERBUATAN MELAWAN HUKUM ATAS PENARIKAN SECARA PAKSA OBJEK JAMINAN FIDUSIA OLEH PT. CAPELLA MULTIDANA - Bunga Khairatunisa; Ulfia Hasanah; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2024)
Unlawful actions refer to any act that violates the law and causes harm to others,obligating the person responsible for the wrongdoing to compensate for the incurred losses. Thecase between Mr. Maman and PT. Capella Multidana involves the forced repossession of Mr.Maman's four-wheeled vehicle due to a 3-month default on installment payments. PT. Capellaused a debt collector without revealing their identity, assignment letter, or membership card fromthe Indonesian Financing Company Association. This study aims to determine whether the forcedrepossession of the fiduciary collateral by PT. Capella Multidana constitutes an unlawful act andto explore potential resolutions.This research is sociological in nature and was conducted at PT. Capella MultidanaPekanbaru City. The study involved three participants: Mr. Maman, Mr. Octa Fadhillah as Mr.Maman's Legal Representative, and the Legal Staff of PT. Capella Multidana. Data collectiontechniques included interviews and literature reviews, utilizing both primary and secondary datasources.PT. Capella Multidana's unlawful actions include the forced repossession of the fiduciarycollateral using a debt collector without proper documentation such as assignment letters,fiduciary deeds, and membership cards from the Indonesian Financing Company Association. Thisact also violated the mutual agreement clause in Article 10 regarding dispute resolution. Mr.Maman suffered losses as a result. The court's decision, with case number 160/pdt.g/pn pbr,ordered PT. Capella Multidana to return Mr. Maman's collateral vehicle. However, PT. CapellaMultidana did not execute the order based on Article 29 of the Fiduciary Guarantee Law, whichincludes direct execution with an executory title, public auction, and private sale. Attempts tonegotiate directly at PT. Capella Multidana's office for a settlement were unsuccessful. Mr.Maman filed a lawsuit that went through the court and the appeal process.Keywords : Keywords: Fiduciary-Withdrawal-Unlawful Actions.